The Effectiveness of Problem Based Learning Pop Up Book to the Mathematic Students Ability on Problem Solving Class VIII - Syaidatul Fitriyah (Universitas Islam Sultan Agung, 2017)
This research is motivated by the lack of mathematical problem solving abilityof students in the material geometry. The purpose of this reseach was to determine the effectiveness of Problem Based Learning (PBL) aided Pop Up book on mathematical problem solving ability of students geometry material.This study was an experimental study where the object of the study was students at MTs. Mujahideen Mluweh class VIII school year 2015/2016. Sampling meggunakan cluster random sampling with the class as a class experiment VIIIA and VIIIB class as the control class. Research data collection techniques using test instruments and observation. The instrument was is test the problem solving and observation instruments. Data were analyzed using regression and T-test.The result of the model Problem Based Learning (PBL) aided Pop Up book on geometry material positive contribution to students' problem-solving abilities. This research is expected to Teachers and Students can apply the model of Problem Based Learning (PBL) aided Pop Up book as an alternative option in mathematics to improve students' problem-solving abilities.